High risk injection drug use and uptake of HIV prevention and treatment services among people who inject drugs in KwaZulu-Natal, South Africa. - Brian C Zanoni; Cecilia Milford; Kedibone Sithole; Nzwakie Mosery; Michael Wilson; Shannon Bosman; Jennifer Smit (PLoS ONE, 2023)
We conducted a mixed-methods study to understand current drug use practices and access to healthcare services for people who use injection drugs in KwaZulu-Natal, South Africa. We used respondent-driven sampling to recruit 45 people who used injection drugs within the past 6 months from KwaZulu-Natal, South Africa. We found high rates of practices that increase HIV/viral hepatitis risk including the use of shared needles (43%) and direct blood injections (bluetoothing) (18%). Despite 35% living with HIV, only 40% accessed antiretroviral therapy within the past year, and one accessed PrEP. None of the participants ever tested for Hepatitis C.